Warehouse location decision in medical sector: A fuzzy comparative study in post-covid era - Tuncalı Yaman, Tutku; Akkartal, Gonca Reyhan (Springer Science and Business Media Deutschland GmbH, 2022)
Without a doubt, the location of the warehouse is a momentous decision in the post-Covid era. Considering a contemporary problem, the authors are aimed to reveal changes in the criteria importance determined in the selection of the warehouse location for the medical products. The difference will be unveiled by comparing the actual situation with the results of a previous study that examined pre-Covid phase evaluations of medical sector professionals and reported the criteria’ importance in ware-house location selection. In the earlier study, the Pythagorean fuzzy (PF)-based-DEMATEL was used to find out the criteria importance. In this study, the importance of the criteria in the warehouse location decisions in the medical sector was revealed by making re-evaluations by a decision-making group consisting of industry professionals. In order to create a proper representation of the post-Covid state, the same methodology was applied in the calculation of criteria importance. Thus, compared to pre-Covid phase, the change in the perceived role of proximity to target markets criterion is found on warehouse location decisions in the medical sector.
Keywords: Drug Logistics; Fuzzy DEMATEL; MCDM; Post-Covid; SCM; Warehouse